(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This article aims to analyze the trajectory of the Núcleo Extensionista Rondon (NER), a University Extension experience developed ten years ago by the State University of Santa Catarina (UDESC). Acting in a decentralized way, the NER inserts students and teachers in the social reality of Santa Catarina, through actions carried out periodically. In its insertions, activities are developed based on the seven axes of University Extension, thus encompassing educational, cultural, social agendas, in addition to other local needs. This article is characterized by the case study method, using the techniques of document analysis, interview and questionnaire for data collection. From the perceptions of students and teachers captured in this work, it is possible to have an idea of ​​the size and relevance of the Center. It can be seen in the responses, that when adding to the academic formation process, the action goes beyond scientific qualification.